Geophysical Investigations at Cairo's Oldest, the Church of Abu Serga (St. Sergius), Cairo, Egypt. Issue 3 (3rd July 2017) - Hemeda, Sayed; Pitilakis, Kyriazis
ABSTRACT: The results of an integrated geophysical survey at the archaeological site of Abu Serga church, Cairo, Egypt are presented and discussed. The aim was to investigate the ground conditions of the Church of Abu Serga (St. Sergius), the Cairo's oldest, dated from 4th Century church, which is located at Qasr el-Shama in old Cairo in Egypt. In particular the objective is to study the subsurface geological structures at the location of the church, and to detect and possibly map any ancient remains concealed under the monument. The survey was conducted using two geophysical methods: the ground penetrating radar (GPR), which is a fully non-destructive method, and the electrical resistivity tomographies (ERTs). The usefulness of combining conventional geophysical mapping techniques and high resolution imaging methods in delineating shallow targets of archaeological interest at such complex archaeological sites, is studied. Ground penetrating radar time slices and 3D electrical tomography depth slices were used for the verification of specific anthropogenic anomalies, which were detected on the geophysical maps Processing of geophysical maps included filtering with the gradient and first derivative operators in the space domain and the upward continuation and Butterworth filters in the wave number domain. The integration of the geophysical measurements revealed that the present Crypt is not the original holy Crypt. The anomalous reflector is detected at depth of about 5 m below the sanctuary floor, in the form of buried ceiling of the original Crypt. The present Crypt is just a small low subterranean church belong to the 2nd century. High resistivity anomalies and distinct GPR signals were also observed deeper in the inner parts of the church. They are attributed to possible remains of ancient walls and surrounding tunnels, or other man-made structures concealed under the floor of the monument. The geophysical survey at Abu Serga church also demonstrates that the general features of the foundation soil are heterogeneous with abundance of fractures; the water table is very high at 1.8m below the sanctuary floors. The benefits of combined geophysical surveys in case of archaeological investigations at complex sites are highlighted.